Evaluating levee setback distance for the co-benefits of groundwater recharge and riparian ecosystem function - Calderwood, Andrew J.; Rodriguez, Alisha; Foglia, Laura; Dahlke, Helen E. (Frontiers in Environmental Science, 2024)
Constructed levees are designed to protect anthropogenic developments from destructive flooding events, but their construction has reduced groundwater recharge, increased flood risk severity under levee failure, increased the incision of river channels, and deteriorated riparian habitat. To reverse these impacts, levee setbacks are often designed to reduce flood risk and provide the opportunity to restore ecohydrological function, while groundwater recharge is rarely considered because it may require relatively detailed groundwater system analysis. In this study, we evaluated 100 heterogeneous hydrogeology realizations to estimate recharge with high-conductivity pathways (HCPs) under varying flood flows for a range of levee setback distances to identify the trade-offs in groundwater recharge and floodplain habitat. We find that on a regional scale, total recharge potential increases with setback distance, with the largest gains up to 1,400 m where there are outcropping HCPs and sufficient flow to inundate more of the setback area. In contrast, the recharge per unit area (i.e., the average daily recharge divided by setback area) generally decreases as levee setback increases, but there are local increases in the recharge per unit area at 1,400 m where HCP recharge may sufficiently offset the larger area. There is a median 10%–40% reduction in peak streamflow with increasing setback distance, which would aid flood risk reduction, but the increased area leads to decreasing depth due to flow losses and increased spreading of flood water. Ultimately, the decision for levee setback distance will depend on local conditions and management goals, as we find that increasing recharge will reduce the floodplain depth necessary for ecosystem function. Our results highlight the opportunity to consider groundwater recharge benefits in levee setback feasibility studies in semi-arid regions impacted by floods and groundwater overdrafts so that setback distance designs can achieve integration of flood risk reduction, riparian habitat, and groundwater recharge.